Uterine didelphys: an incidental finding during caesarean section - Pillai, Reena N. R.; Amma, Sai L. S. K.; Kutty, Sathiamma P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Mullerian duct anomalies are congenital defects of the female reproductive system resulting from abnormal embryological development. Uterine didelphys occurs due to the failure of embryonic fusion of the Mullerian ducts. This results in the presence of a double uterus with two separate cervices, and often a double vagina; it is extremely rare and can have unpredictable effects on reproductive health and gestation. We report a case of accidental finding of uterine didelphys in a 27-year-old gravida 5 para 4 live 3 with previous three term vaginal deliveries and one caesarean section with history of tubal sterilization, during caesarean section.